2018
DOI: 10.4103/jmu.jmu_5_17
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of some abdominal organs in sickle cell disease patients in a tertiary health institution in Northeastern Nigeria

Abstract: Background:Sonographic evaluation of abdominal organs is an important work up in managing sickle cell disease (SCD) patients. This study aimed at evaluating abdominal organs by sonography among SCD patients.Methodology:A cross-sectional study was carried out in Maiduguri, Nigeria from April 2014 to July 2015. Two hundred and fifty-two patients participated in the study, with 126 controls and 126 SCD patients. There were 131 (52%) males, and 121 (48%) females, with age range 3–38 years. Measurements were done u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 13 publications
3
22
1
Order By: Relevance
“…Our findings were consistent with previous reports in terms of renal length but not cortical echogenicty. 17,29,30 The increase in cortical echogenicity in this study could have been due to many variables, such as the experience of the US operator, sample size, type of US machine, and stage of disease progression. Other factors include multiple small scatter reflectors from vascular intimal hyperplasia, thrombosis, higher blood flow in anemic patients, and the presence of microvascular sickled red blood cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings were consistent with previous reports in terms of renal length but not cortical echogenicty. 17,29,30 The increase in cortical echogenicity in this study could have been due to many variables, such as the experience of the US operator, sample size, type of US machine, and stage of disease progression. Other factors include multiple small scatter reflectors from vascular intimal hyperplasia, thrombosis, higher blood flow in anemic patients, and the presence of microvascular sickled red blood cells.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, 59 (90.8%) patients had mildly diffuse increased cortical echogenicity with preserved renal cortical thickness, and 6 (9.2%) had normal cortical echogenicity and thickness. Our findings were consistent with previous reports in terms of renal length but not cortical echogenicty . The increase in cortical echogenicity in this study could have been due to many variables, such as the experience of the US operator, sample size, type of US machine, and stage of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…We read the publication on “sonographic evaluation of some abdominal organs in sickle cell disease (SCD) patients in a tertiary health institution in Northeastern Nigeria” with a great interest. [1] Luntsi et al . reported that “abdominal sonography in SCD patients revealed varied remarkable changes in the size, echotexture, intraluminal deposits, and wall thickness in the liver, gallbladder, kidneys, and spleen.”[1] We would like to share the ideas on this report.…”
mentioning
confidence: 99%
“…[1] Luntsi et al . reported that “abdominal sonography in SCD patients revealed varied remarkable changes in the size, echotexture, intraluminal deposits, and wall thickness in the liver, gallbladder, kidneys, and spleen.”[1] We would like to share the ideas on this report. First, without screening for other common diseases such as hepatitis or metabolic disease, the finding might be the result from other confounding disorders.…”
mentioning
confidence: 99%
“…In our study, we reported that “Assessment of abdominal organs such as the liver, gallbladder, spleen, and kidneys by ultrasound among sickle cell disease (SCD) patients revealed varied remarkable changes in these organ sizes, echotexture, intraluminal deposits, and wall thickness among the studied patients. Abdominal sonography is an easy, affordable, readily available, accurate, and noninvasive diagnostic tool for early detection of organ changes for further management and follow-up of SCD patients.”[1]…”
mentioning
confidence: 99%